Peran akun twitter @literarybase dalam meningkatkan minat baca followersnya - Sakawuni Maghfira Firdestia Bunga; Margareta Aulia Rachman (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. @literarybase is an autobase account focusing on literacy and literature on Twitter. This article discusses the role of @literarybase in increasing the reading interest of its followers based on principles of reading interest development. Data Collection Methods. This study used a quantitative approach with survey method as the data collection technique involving 288 followers of @literarybase account. Data Analysis. The data was analyzed using a descriptive analysis method. Results and Discussion. The results showed that the @literarybase account played a significant role as a place to increase followers' reading interest. In general, the @literarybase account has applied the principles of reading interest development framework. Conclusion. Based on the findings, the application of the principle of teaching interest self-regulation strategies on the @literarybase account is still not as effective as the other three on reading interest development principles.In managing the account, the @literarybase, more interactivediscussions with their followers to support activities related to literacy and literature.